Stressors and Coping Mechanisms of Teachers: ISBN 978-606-95069-4-3 - Pagulong, Cesar J.; Bulilawa, Rafunzel Y. (Technium Books, 2021)
This study aimed to assess the stressors and coping mechanisms of Senior High School (SHS) Teachers. Moreover, it aimed to establish the difference between the stressors and coping mechanisms of Senior High School teachers in Tagbilaran City Schools Division, Tagbilaran City, Bohol, Philippines. Specifically, it determined the significant difference in the respondents’ stressors and coping mechanisms when categorized according to age and gender. Based on the assessment and findings, stress management measures are proposed. The respondents of this study were the Public Senior High School (SHS) Teachers of Tagbilaran City Schools Division, Tagbilaran City, Bohol. No sampling technique was used because the total population of teachers participated in the study. The descriptive-correlational in nature. It employed a questionnaire in gathering the data to measure stressors and coping mechanisms used by the respondents. The researcher found that teachers are stressed if the physical working environment is not conducive to learning and teaching. Moreover, lack of resource materials and other paperwork related can really affect the teachers mentally. On the other hand, emotional and social stressors did not affect too much, although teachers have encountered these stressors while in school. Thus, the respondents’ stressors and coping mechanisms used by the teachers have no significant difference when categorized according to age and sex except for the physical coping in terms of gender. Youtube video link https://youtu.be/5E8JndGQkNM Technium Books publish all content in open access, promoting the exchange of ideas and knowledge in a globalized world. Technium Books encompasses all the benefits of open access—high availability and visibility, as well as wide and rapid dissemination. Technium Books are distributed under the terms and conditions of the Creative Commons Attribution License — as an author, you retain the copyright for your work. Technium Books believes that the contemporary wave in academia of wider and faster dissemination of knowledge with open access should not be restricted to academic journals but should also capture and elevate academic & research book publishing. See visitor map: https://clustrmaps.com/site/1bg5q